Haemophilus - Munson, Robert (Henry Stewart Talks, 2009)
Hemophilus influenzae, Virulence determinants, Immunization strategies, Hib, Other serotypes, Basic structure of the H. influenzae LOS, Sialic acids and virulence, Phosphorylcholine (PCho) and virulence, Phase variable genes, Iron utilization systems, Resistance to effectors of innate immunity, Adhesins, Other Haemophilus species associated with human health and disease, Haemophilus ducreyi
Archived at 2025/05/28